Sedimente von vier Hochgebirgsseen unter unterschiedlichem Einfluß von Permafrost - Tolotti, M.; Nickus, U.; Thies, H. (country:IT, 2015)
A paleolimnological survey of high mountain lakes in North- and South-Tyrol was conducted within the Interreg project Permaqua (permafrost and its effects on water balance and mountain water ecology) aiming at econstructing the ecological evolution of lakes in permafrost regions since the end of the Little ice Age (~1850), and to investigate possible effects of permafrost thawing on lake geochemistry and biology. Sediment cores from four lakes located above ~2500 m a.s.l. on crystalline bedrock were radioistopically dated (210Pb, 226Ra, 137Cs and 241Am and 14C) and analyzed for lithological (wet density, water and organic content), geochemical (principal elements and heavy metals), and biological (diatom abundance and speceis composition) proxies. All the cores studied showed lithological and biological changes between the end of the Little Ice Age and the first decades of the 20th century. Concentrations of heavy metals increased in the studied cores during the last ~ 150 years and reached highest values after the 1990s. On the contray, changes in diatom species composition which typically characterize many lower lakes of the northern hemisphere after the economic development in the 1960s were not recorded in the lakes investigated. However, it is not possible to explain these changes as completely related to the presence of active rock glaciers in the lake catchments. The long-term changes of biological and chemical indicators observed in the studied sediment cores appear to be the results of a set of combined factors, such as geochemistry, weathering, or catchment characteristics.